ANALISIS USER EXPERIENCE UNTUK MENGOPTIMASI APLIKASI PRODESKEL DI KOTA PALEMBANG - Sari, Nursella; Gustriansyah, Rendra; Mair, Zaid Romegar (IDEALIS : InDonEsiA journaL Information System, 2024)
Prodeskel is a site-based application and used as an information center for data related to Villages and Subdistricts. All villages and sub-districts in Indonesia use Prodeskel, so the large number of users of Prodeskel causes frequent errors in application which give rise to complaints from users, likewise the city of Palembang, to overcome this problem it’s necessary to improve the quality of Prodeskel through user experience. Therefore, this study analyzes user experience on Prodeskel using three methods, namely, SUS, UEQ and Heart Metrics. SUS method can be used easily and helps in evaluating a system,UEQ provides analysis tools that are accurate and easy to interpret, and Heart Metrics can easily identify goals and success of the application. Dapil 4-6 of Palembang City became the research location because this area was easy to cover, by distributing questionnaire forms via WhatsApp to users, with a total of 45 respondents. SUS, the calculation results obtained a total score of 65. UEQ obtained an average value of >0.8, which means variables had positive values. Meanwhile, Heart Metrics, it was found that there were two variables that had a high level of usefulness, namely engagement and retention, while the other three variables had a very high level of usefulness. Based on the analysis results, obstacles received by users in using this application are the level of active use and ease of application. With this research, it’is hoped that in quality of the application will be improved so that there will be no complaints from users.